EFFECT OF NITROGEN AND PANCHAGAVYA ON GROWTH AND YIELD OF BABY CORN (Zea mays L.) - S .SREETHU,; SHIKHA SINGH, (The Bioscan, 2020)
The study was aimed to analyse the effect of nitrogen and panchagavya on growth and yield of Baby corn (Zea mays L.). Among the treatments 60 kg N + 4 sprays of 3% Panchagavya was superior than the rest and recorded the maximum plant height (117.67cm), dry matter accumulation (1466.52 g/m 2 ), leaf area index (8.00), crop growth rate (41.48 g/m 2 /day), number of cobs per plant (2.14), number of cobs/ha (166296.3), yield with husk (261.39 q/ha),yield without husk (53.71q/ha) and greenfodder yield (37t/ha) in baby corn. The present investigation revealed that 60 kg N + 4 sprays of 3% Panchagavya would produce maximum growth and yield attributes and can be recommended for baby corn cultivation.